Surveying Civilization Teachers’ Methods and Techniques: case study of Master one Students_ Department of English - Laghouat University - Slimani ,kheira; Gasmi ,Mustapha (Faculty of Letters and Foreign Languages Department of English, 2018)
Civilization has become one of the most important topics in teaching English as a foreign language. In this case , the teaching of British and American civilizations are one of the main important modules in the department of English at Laghouat university, which is supposed to make the learners familiar with the target language’s culture, develop their critical thinking , also to enhance their communicative skills . The purpose of this study is to investigate if the teachers of civilization make use of the different methods and techniques of teaching civilization courses. The method of this research involves students’ questionnaire, that aimed to examine the students’ views about the teaching methods and techniques that are used by their teachers of civilization. The findings of this research have revealed that teachers of civilization in the department of English at Laghouat University are making use of the different methods and techniques that should be used to teach civilization courses to the learners of English as a foreign language.